Complete chloroplast genome sequence of Ligustrum quihoui (Oleaceae): genome structure and genomic resources - Wang, Lei (Mitochondrial DNA B Resour, 2019)
Ligustrum quihoui is popular as landscape plants used as hedges in gardens. In this study, we sequenced the complete chloroplast genome of L. quihoui based on next-generation sequencing and used the data to assess genomic resources. The chloroplast genome of L. quihoui is 163,575 bp in length consisting of large and small single-copy regions of length 88,072 and 11,493 bp, separated by two IR regions of 32,005 bp. De novo assembly and annotation showed the presence of 115 unique genes with 81 protein-coding genes, 30 tRNA genes, and four rRNA genes. A total of 62 perfect chloroplast simple sequence repeats were analyzed in the L. quihoui. A maximum-likelihood phylogenomic analysis showed that L. quihoui was sister to L. gracile.